Professional apprenticeship of adult-child interaction - Novo, Rosa (2011)
Using the adult engagement scale (Laevers, 1994), this poster analyzes the development of educational interactions of two trainee-educators in the final teaching practice of the pre-school educator degree which is implemented in different supervising contexts. A first aim is to understand the educational interaction with reference to the pedagogical option adopted in the supervising context. A second aim is to identify similarities and differences in the interaction competences of the trainees. A multi-context study of qualitative, evaluative nature allowed the understanding of the relation between the quality of supervised contexts with the learnings of preschool teacher trainees. Among the conclusions drawn from data, the interactivity between the learnings of pre-school teacher trainees, the supervised contexts where training takes place and the pedagogical grammar adopted in the training context is to be emphasized. It is also to be emphasized that learning to interact is a long lasting process that requires the learning of complex nature skills. It should furthermore be emphasized that not all practical training is a sufficient guarantee to a participative pedagogy. A need for further research in this area is still forwarded.